Epidemiology of drowning deaths in the Philippines, 1980 to 2011 - Rammell Eric Martinez; John Juliard Go; Jonathan Guevarra (World Health Organization Regional Office for the Western Pacific, 2016)
Drowning kills 372 000 people yearly worldwide and is a serious public health issue in the Philippines. This study aims to determine if the drowning death rates in the Philippine Health Statistics (PHS) reports from 1980 to 2011 were underestimated. A retrospective descriptive study was conducted to describe the trend of deaths caused by drowning in the Philippines from official and unofficial sources in the period 1980 to 2011. Information about deaths related to cataclysmic causes, particularly victims of storms and floods, and maritime accidents in the Philippines during the study period were reviewed and compared with the PHS drowning death data. An average of 2496 deaths per year caused by drowning were recorded in the PHS reports from 1980 to 2011 (range 671-3656). The average death rate was 3.5/100 000 population (range 1.3-4.7). An average of 4196 drowning deaths were recorded from 1980 to 2011 (range 1220 to 8788) when catacylsmic events and maritime accidents were combined with PHS data. The average death rate was 6/100 000 population (range 2.5-14.2). Our results showed that on average there were 1700 more drowning deaths per year when deaths caused by cataclysms and maritime accidents were added to the PHS data. This illustrated that drowning deaths were underestimated in the official surveillance data. Passive surveillance and irregular data management are contributing to underestimation of drowning in the Philippines. Additionally, deaths due to flooding, storms and maritime accidents are not counted as drowning deaths, which further contributes to the underestimation. Surveillance of drowning data can be improved using more precise case definitions and a multisectoral approach.